Considerations in Forming Operations - Atwater, Mark (McGraw-Hill Education, 2018)
This project examines the factors that affect forming operations in manufacturing, such as forging, rolling, extruding, and vacuum forming. The role of plasticity, yield strength, and elasticity are emphasized. Students explore the concept of ductility and its connection to percent elongation.